化简 x-y/(y-x)^3=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 16:52:32
化简x-y/(y-x)^3=化简x-y/(y-x)^3=化简x-y/(y-x)^3=(x-y)/(y-x)^3=(x-y)/[-(x-y)^3]=-1/(x-y)^2原式=-1/(x-y)^2原式=(
化简 x-y/(y-x)^3=
化简 x-y/(y-x)^3=
化简 x-y/(y-x)^3=
(x-y)/(y-x)^3=(x-y)/[-(x-y)^3]=-1/(x-y)^2
原式=-1/(x-y)^2
原式=(-1)(y-x)/(y-x)^3=(-1)/(y-x)^2
(x-y)/(y-x)^3=(x-y)/[-(x-y)^3]=-1/(x-y)^2 这个是对的
化简 x / y(x+y) - y / x(x+y) =
化简 x-y/(y-x)^3=
化简3x-2/(x+y)[(x+y)/3x-x-y]÷(x-y)/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1
化简:(x-3y)(x+y)-(x-2y)(x+2y)-(x-y)平方
(x+y-5)*(x+y-5)+(x-y+3)=0 x*x-y*y
已知:3x-5y=0,求x/y,x-y/y,x-y/x
推倒公式:(x+y)(x*x-3x+y*y)=x*x*x+y*y*y怎么做.
化简:5(x-y)+2(x+y)-3(x-y)
化简3(x-y)-7(x--y)+2(y-x)
x^/y-x-y^/y-x化简.
化简x(y-x)-y(x-y)
化简(2x^3y^3+x^4y^2+x^2y^4)^2-x^2y^2(x+y)^2,x=2012,y=-2011
化简:【(x-y)的2次方+(x+y)(x-y)】除以2x,其中x=3,y=1.5
化简,求值:[(x/y)-(y/x)]除以[(x/y)+(y/x)-2]除以[1+(y/x)],其中x=1/2,y=1/3
(x+y)-(x-y)^3÷(x-y)(x+y)×2y化简e ,
(x+y)(x-y)+(x-y)平方-(x-y)(3x-y) 其中x=-2 y=3分之一